The Impact of Artificial Intelligence on the Construction of Identity and Personal Autonomy (Islas, 2025)
Introduction: This paper analyzes how certain algorithmic systems affect the construction of personal identity and autonomy in digital environments. A philosophical and legal approach is adopted, with attention to recent examples of practical impact.Methods: The study employs a qualitative methodology based on critical analysis of specialized literature and case studies that illustrate the effects of technologies such as recommendation algorithms, facial recognition, and social scoring systems.Results: The analysis shows that algorithmic systems condition the visibility and validation of digital identities, amplify pre-existing biases, and limit the critical autonomy of individuals in the digital space.Conclusions: The paper proposes moving toward regulatory frameworks that ensure the transparency, intelligibility, and verifiability of algorithmic systems, integrating a comparative approach and ethical principles to ensure the effective protection of personal identity.
Keywords: digital identity; personal autonomy; artificial intelligence; algorithmic surveillance; digital inequality